Transforming Family Privacy: Floridi and Nissenbaum on Digital Ethics - Yesilkaya, Nazan (Şırnak Univ, 2025)
This study uniquely focuses on the transformation of privacy in the digital age from an ethical perspective within the context of family structure. With the widespread use of digital technologies, privacy has evolved from a fixed and protected space to a structure that is shaped by context, permeable, and fragile. Social media platforms, in particular, have disrupted family privacy, blurring the boundaries between private life and public visibility, rendering family members constantly visible and traceable. The study explores the tension between the normative values of the digital age and intra-family privacy at both conceptual and theoretical levels. Theoretical analysis was employed as the method, and Luciano Floridi's information ethics and Helen Nisenbaum's contextual integrity theories served as the foundational theoretical framework. Floridi defines the individual as an information entity in the digital universe and considers privacy as an ethical domain of existence. Nissenbaum, on the other hand, approaches privacy as an issue of integrity based on norms related to the appropriate transmission of information within a social context. In the literature, digital privacy is often discussed in terms of individual privacy, data security, or user behaviour. However, the evaluation of privacy within the family structure in the context of digitalisation using ethical theories is a limited field. This study aims to fill this gap by adopting an interdisciplinary approach that integrates digital ethical theories with other relevant disciplines. In conclusion, family privacy in the digital age is not merely a value to be protected but also an active and controversial area of existence that urgently requires the establishment of new digital ethical norms and social responsibility.
Keywords: History of Philosophy; Digital Ethics; Information Ethics; Contextual Integrity; Privacy; Family Structure